Broad Mite, Polyphagotarsonemus latus (Banks) (Arachnida: Acari: Tarsonemidae) - Thomas R. Fasulo (EDIS)
The broad mite, Polyphagotarsonemus latus, was first described by Banks (1904) as Tarsonemus latus from the terminal buds of mango in a greenhouse in Washington, D.C., USA (Denmark 1980). This species has a large host range world-wide. This document is EENY-183 (IN340), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2000. Revised: September 2005.